2017
DOI: 10.5380/ce.v21i4.37651
|View full text |Cite
|
Sign up to set email alerts
|

Presença Do Acompanhante De Livre Escolha No Processo Parturitivo: Repercussões Na Assistência Obstétrica

Abstract: Objetivou-se identificar a prevalência da presença do acompanhante escolhido pela mulher nas fases do processo parturitivo e analisar as associações da presença do acompanhante na assistência obstétrica. Pesquisa quantitativa, retrospectiva de análise documental do banco de dados de um estudo primário, em três maternidades públicas do município de Niterói, Rio de Janeiro, executado em 2014. O Teste de Associação de Qui- quadrado (α = 0,05) foi utilizado tendo o Statistical Package for Social Science for Window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
4
Order By: Relevance
“…2,15 Pregnant women generally arrive at maternity hospitals accompanied upon admission; however, gradual separation can be observed, depending on the evolution of the stages of the parturition process, and this may be related to companions not being included in the hospital routine. 16 In order for pregnant/parturient women to have access to continuous support from their companions, companions need to receive information, be included in health education activities performed in groups and included in prenatal care sessions. 17 Despite this, national studies on data from the Nascer no Brasil (Being Born in Brazil) survey (2011/2012), demonstrated that 24.5% of women did not have a Yaná Tamara Tomasi et al companion present during childbirth -this being 2.7 times greater than the prevalence found in this studyand only 19.3% had a companion present at all times during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,15 Pregnant women generally arrive at maternity hospitals accompanied upon admission; however, gradual separation can be observed, depending on the evolution of the stages of the parturition process, and this may be related to companions not being included in the hospital routine. 16 In order for pregnant/parturient women to have access to continuous support from their companions, companions need to receive information, be included in health education activities performed in groups and included in prenatal care sessions. 17 Despite this, national studies on data from the Nascer no Brasil (Being Born in Brazil) survey (2011/2012), demonstrated that 24.5% of women did not have a Yaná Tamara Tomasi et al companion present during childbirth -this being 2.7 times greater than the prevalence found in this studyand only 19.3% had a companion present at all times during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…This result was also indicated by a study conducted in three public maternity hospitals in the municipality of Niterói, RJ, which found greater occurrence of massaging, bathing, breathing and movement techniques among parturient women accompanied by companions they had chosen freely. 16 Good labor and childbirth practices provide guidance on what should or should not be done during the childbirth process. Practices identified as obstetric violence are discouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo que não mensurados o contexto e os motivos da ausência dos acompanhantes nos cenários elencados, sugerem-se fortes relações com a adoção de rotinas hospitalares nas Unidades de Saúde, que não favorecem o acompanhamento por pessoa de livre escolha da mulher durante o processo parturitivo, contrariando a legislação vigente. 8 É necessário que as mudanças nas rotinas do centro obstétrico sejam planejadas e implementadas, de maneira que a participação do acompanhante seja efetiva em todos os momentos do parto. 25 Outro aspecto que emergiu das evidências (A4; A18) está relacionado com a falta de apoio institucional, sendo este um dos motivos que limita a presença do acompanhante.…”
Section: Métodounclassified
“…Fator(es) relacionado(s) a algum tipo de violência obstétrica Estratégias para empoderar gestantes contra a violência obstétrica Presença do acompanhante de livre escolha no processo parturitivo: Repercussões na assistência obstétrica, 2017 (Dulfe et al, 2017).…”
Section: Títulounclassified